Blind estimation of encoder structure under non-cooperative environment - Cheng, Shan. (2009)
This project is about the simulation of the process of blind estimation of block code encoder structure under non-cooperative environment. We estimate the encoder structure through the analysis of the linear algebra properties of the received data sequence